Superinfecção pelo HIV-1: uma breve revisão da literatura - Tibúrcio, Alberto Saraiva; Salles, Roberto S.; Passos, Felipe D.L. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: the HIV-1 superinfection can occur with strains of the same subtype (intrassubtype), with strains of different subtypes (intersubtype) in group M, between different groups (M, N, O) and with HIV-2. The true incidence of superinfection is uncertain because it depends on factors related to the host, the infectious agent, the type of study and methodologies used to detect the phenomenon. Objective: answer the following questions: What is the evidence of the existence of HIV-1 superinfection? At what time does superinfection occur? Under what conditions can superinfection occur? What are the consequences of superinfection for a person already carrying the HIV-1 and for the Public Health? Methods: bibliography of articles published in scientific journals available online, located by PubMed, Medscape, SciELO and Lilacs on the subject of re-infection / superinfection by HIV-1 in the period between 2000 and 2010. The articles used as reference address those questions listed by the author in the Objective. Results: four studies have attempted to assess the time of superinfection, which occurred during the acute infection or after the establishment of immune responses; there was correlation between sudden elevation of viral load and superinfection in two studies; three studies showed that the immune response to primary infection was not sufficient to protect against reinfection; a study has found that coinfection and superinfection had a worse prognosis. Conclusion: the incidence of reinfection and the appearance of recombination are well evidenced with the current techniques of molecular biology. Reinfections have been shown both in the initial stage and in the later stages of the HIV-1 infection. More factors related to individuals and to HIV-1 need to be investigated to determine more precisely the conditions that lead to reinfection. Recombination, with increase of the viral pathogenicity, is the most feared consequence of superinfection.